2010
DOI: 10.2353/ajpath.2010.090268
|View full text |Cite
|
Sign up to set email alerts
|

Human Nephrosclerosis Triggers a Hypoxia-Related Glomerulopathy

Abstract: In the kidney, hypoxia contributes to tubulointerstitial fibrosis, but little is known about its implications for glomerular damage and glomerulosclerosis. Chronic hypoxia was hypothesized to be involved in nephrosclerosis (NSC) or "hypertensive nephropathy." In the present study genome-wide expression data from microdissected glomeruli were studied to examine the role of hypoxia in glomerulosclerosis of human NSC. Functional annotation analysis revealed prominent regulation of hypoxia-associated biological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 70 publications
(94 reference statements)
2
86
2
Order By: Relevance
“…HIF is a key transcription factor which regulates adaptive responses to hypoxia. They demonstrated that the HIF target gene, chemokine receptor C-X-C motif receptor (CXCR4), 4 was prominently increased in podocytes, and HIF-1α showed nuclear localization, which was indicative of HIF activation [10]. Ding et al also showed that forced HIF stabilization by deletion of the Von Hippel-Lindau gene induced CXCR4 in the glomeruli and resulted in necrotizing crescentic glomerulonephritis [11].…”
Section: Introductionmentioning
confidence: 99%
“…HIF is a key transcription factor which regulates adaptive responses to hypoxia. They demonstrated that the HIF target gene, chemokine receptor C-X-C motif receptor (CXCR4), 4 was prominently increased in podocytes, and HIF-1α showed nuclear localization, which was indicative of HIF activation [10]. Ding et al also showed that forced HIF stabilization by deletion of the Von Hippel-Lindau gene induced CXCR4 in the glomeruli and resulted in necrotizing crescentic glomerulonephritis [11].…”
Section: Introductionmentioning
confidence: 99%
“…nephromine.org). 12,13,23,24 Effective BMP7 treatment of UUO and DN mice (decreased fibrosis) correlated with normalization of Tet3 expression levels ( Figure 1K). In summary, fibrosis was associated with Rasal1 promoter hypermethylation, suppressed Rasal1 expression, and suppressed Tet3 expression (expression of Tet1 and Tet2 were not substantially altered), whereas amelioration of fibrosis was associated with normalization of Rasal1 promoter methylation and Rasal1 expression, de novo hydroxymethylation of Rasal1 promoter, and increased Tet3 expression (Tet1 and Tet2 expression levels were not increased).…”
mentioning
confidence: 99%
“…In this regard, transcriptome analysis data on larger cohorts available through the Nephromine database (www.nephromine.org) reveal that CKD caused by minimal change nephropathy and hypertensive nephrosclerosis correlated with decreased RASAL1 expression. [11][12][13] In summary, our results suggest that RASAL1 is hypermethylated in kidney fibrosis, irrespective of the underlying cause, and based on our data, testing the use of RASAL1 methylation as a biomarker of CKD in larger cohorts of patients may deserve consideration.…”
mentioning
confidence: 99%
“…Increasing evidence indicates that excessive reactive oxygen species (ROS) induced by chronic hyperglycaemia play a central role in the development of diabetic complications [1][2][3]. ROS can activate several proinflammatory transcriptional factors, resulting in the production of cytokines, chemokines and adhesion molecules, as well as an influx of inflammatory cells into the kidney [4,5]. The importance of redox balance in diabetic nephropathy has been demonstrated in diabetic mice overexpressing antioxidant enzymes; these animals are protected from interstitial fibrosis and their proximal tubule cells do not undergo apoptosis [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%